Factors differentiating change of direction performance in NCAA power 4 male basketball athletes - Petway, A. J.; Harper, D.; Cohen, D.; Eriksrud, O. (International Journal of Sports Science & Coaching, 2025)
The aim of this study was to investigate COD performance in an elite basketball cohort to determine which phase specific qualities are most strongly associated with COD performance. One hundred and twenty-four male basketball athletes (age = 20.9 ± 1.23 years, height = 195 ± 14.3 cm, body mass = 89.9 ± 10.2 kg) from 10 different NCAA Power 4 basketball programs participated in this study. COD performance was assessed using a modified 505 (m505) COD test with phase specific and overall COD performance times measured via a portable motorized resistance device. Multiple linear regression was used to explore how total time to complete the m505 was influenced by the different phase-specific outcome measurements and differences between bigs (n = 54) and guards (n = 70) calculated using independent t-tests and Cohen's effect size. Four phase specific COD metrics significantly associated with m505 COD time to completion, including: time phase 1a (r = 0.90, p < 0.001), time phase 1b (r = 0.77, p < 0.001), maximal acceleration 1a (r = -0.73, p < 0.001) and maximal deceleration (r = -0.42, p < 0.001). These findings highlight the importance of phase specific outcome measures when assessing COD performance in elite basketball athletes.